Solução para cristalização de produto em formulador a baixas temperaturas - Gameiro, Danielle Gutschow (2022)
In a pesticide production industry, a proposal was submitted to produce a herbicide from a competing company through outsourcing. For this, it will be necessary to adapt the current plant of the factory, avoiding the crystallization of the product in the formulator on cold days, and proposing a solution for the filling required in isotanks. The proposed solution was the implementation of a filling station, in isotanks, close to the factory. Moreover, when discussing different solutions to avoid product crystallization in the formulator, the most appropriate proposal for the company's needs was the installation of a plate heat exchanger in the formulator's recirculation line. This proposal included three control systems, two of the proportional integral and derivative control type (PID), and one of the on-off type. The PID controls were evaluated in the Anaconda Distribution program (version 2021.11) through simulation in python language and the setpoint values were reached with the suggested control. Through the proposed solution, it is possible to carry out the production of the required product without the occurrence of crystallization and the inclusion of control systems increases safety and reduces process time by increasing capacity.